2020
DOI: 10.1038/s41598-020-72677-1
|View full text |Cite
|
Sign up to set email alerts
|

Work functioning impairment in the course of pharmacotherapy treatment for depression

Abstract: This study investigated the association between the duration of pharmacotherapy treatment for depression, or discontinuation from treatment, and work functioning impairment. This was a retrospective cohort study examining 30,409 workers. Work functioning impairment was assessed using a questionnaire, and treatment status was assessed using medical claims data. Odds ratios (ORs) of workers with severe work functioning impairment compared with healthy workers (control group) were calculated using logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The finding about medication is consistent with a previous study of depression, which showed that depressed employees often experience long-term loss of work performance when they run out of drugs. 30 Our study also demonstrated that disruptions in routine clinical settings showed a relatively weak association with reduced productivity at work (aOR 1.67) when compared with running out of drugs (aOR 2.58) or disruptions in non-routine clinical settings (aOR 2.34). Family doctors tried to offer patients routine care visits during the COVID-19 pandemic whenever they showed symptoms of exacerbated clinical conditions.…”
Section: Discussionsupporting
confidence: 51%
“…The finding about medication is consistent with a previous study of depression, which showed that depressed employees often experience long-term loss of work performance when they run out of drugs. 30 Our study also demonstrated that disruptions in routine clinical settings showed a relatively weak association with reduced productivity at work (aOR 1.67) when compared with running out of drugs (aOR 2.58) or disruptions in non-routine clinical settings (aOR 2.34). Family doctors tried to offer patients routine care visits during the COVID-19 pandemic whenever they showed symptoms of exacerbated clinical conditions.…”
Section: Discussionsupporting
confidence: 51%
“…35 The lack of benefit on work/studies is likely to be explained by the short duration of the present studies (6 weeks), because patients with depression, especially those with inadequate response to ADT, are prone to persistent impairment in occupational functioning. [36][37][38] This persistent impairment may be attributed to residual cognitive symptoms, such as impaired attention, executive function, and verbal memory, as well as the adverse effects of antidepressant medications. [38][39][40] With regard to dosing, the effects of the brexpiprazole 2 mg and 2 to 3 mg doses were generally similar, although a greater number of MADRS items had P < 0.05 versus placebo in the 2 to 3 mg analysis, likely reflecting the larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Longer shared family time can improve the relationship within the family; promoting the mental health of family members and reducing the degree of depression [16]. Depression patients are often accompanied by varying degrees of work capacity loss [17]. The lack of parental affection and the reduction of communication with parents (usually when the medical workers are parents) will also significantly affect the physical and mental development of children [18] because parent-child interaction is an important regulatory way to support children's continuous development [19].…”
Section: Discussionmentioning
confidence: 99%